The Domestic Violence Treatment Option in Whitehorse, Yukon: Final Evaluation Report - Hornick, J.P.; Boyes, M.; Tutty, L.; White, L. (National Crime Prevention Centre., 2005)
A quasi-experimental pre-test post-test group design was used in this study. Given the complexity of the DVTO program and the three different routes for entry into the SAP (i.e., DVTO program, sentencing requirement after trial, or self-referral), this was the most appropriate design. During the pre-test, as part of the assessment, data were collected from both offenders and victims. These data served as a baseline for later comparisons with post-test data. The post-test data were collected from offenders at the end of the 10-week treatment program. All data were input directly into a computer Management Information System (MIS) developed specifically for the project. Data were collected from June 2002 to November 2004. Follow-up of reports of reoffending for the offenders continued until the end of the project using various police information systems. The original plan was also to follow victims three months and six months after completion of the program to identify whether there were unreported reoccurrences. Unfortunately, victims, for the most part, chose not to become involved.